Women Entrepreneurship in Croatia in International Perspective (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Differences in entrepreneurial activity between women and men arise from the cultural context and from the role of women in family life. Although the Constitution of the Republic of Croatia guarantees gender equality and all equal rights for both men and women, differences between men and women still exist, especially when looking at indicators related to the labor market, the possibility of advancement and the possibility of harmonizing private and business life. Women make up 51% of the total population in Europe, and 51.5% in the Republic of Croatia. This natural balance (with a small preponderance of women) is not present in the business or political sphere of activity. The purpose of this paper is to show the entrepreneurial activity of women in Croatia and to give insight into programs and projects to encourage the development of women in entrepreneurship. Furthermore, the paper will show the differences between men and women in four dimensions: economic inclusion and economic opportunities, education, health and life expectancy, and political empowerment.